The impossible climb : Alex Honnold, El Capitan, and a climber's life - Synnott, Hampton (Viking, 2022)
Provides an adapted biography of Alex Honnold, known for his record-setting free solo assent up El Capitan in Yosemite National Park. Highlights moments from his early climbing days and those leading up to the greatest climb of his life to date.